Analysis of efficacy of lenvatinib treatment in highly advanced hepatocellular carcinoma with tumor thrombus in the main trunk of the portal vein or tumor with more than 50% liver occupation: A multicenter analysis. Issue 2 (5th January 2021) - Chuma, Makoto; Uojima, Haruki; Hiraoka, Atsushi; Kobayashi, Satoshi; Toyoda, Hidenori; Tada, Toshifumi; Hidaka, Hisashi; Iwabuchi, Shogo; Numata, Kazushi; Itobayashi, Ei; Itokawa, Norio; Kariyama, Kazuya; et al.
Abstract : Aims: To assess the safety, efficacy, and prognostic impact of clinical factors associated with lenvatinib treatment in highly advanced hepatocellular carcinoma (HCC) with tumor thrombus in the main portal vein trunk (VP4) or tumor with more than 50% liver occupation (tm50%LO). Methods: A total of 61 highly advanced HCC patients (41 patients with tm50%LO and 20 patients with VP4) who were treated with lenvatinib at multicenter were enrolled and retrospectively analyzed for treatment outcomes according to their clinical status, including tumor morphology. Results: The most frequent grade ≥3 adverse event in tm50%LO HCC was elevated aspartate aminotransferase (17.1%). Objective response rates were 37.5% and 0% in tm50%LO HCC patients with Child–Pugh grade (CP)‐A and CP‐B, respectively, and 26.7% and 0% in VP4 HCC patients with CP‐A and CP‐B, respectively. Estimated median progression‐free survival and overall survival were 132 days and 229 days, and 101 days and 201 days in patients with tm50%LO and VP4, respectively. In multivariate analysis, modified albumin‐bilirubin grade (hazard ratio 0.372, 95% CI 0.157–0.887; p = 0.0241) and tumor morphology (hazard ratio 0.322, 95% CI 0.116–0.889; p = 0.0287) were independently associated with progression‐free survival in patients with tm50%LO HCC. In VP4 HCC, median progression‐free survival was worse in CP‐B (57 days) than in CP‐A patients (137 days, p = 0.0462). Conclusions: Lenvatinib treatment offers a benefit in highly advanced HCC (tm50%LO or VP4) patients with good liver function or nodular‐type tumor. The various characteristics identified in this study might be useful as indicators of lenvatinib treatment in highly advanced HCC with tm50%LO or VP4, which are considered very refractory cancers.